1988
DOI: 10.1002/ana.410240510
|View full text |Cite
|
Sign up to set email alerts
|

Neurological abnormalities associated with remote occupational elemental mercury exposure

Abstract: We examined 502 subjects, 247 of whom had occupational elemental mercury exposures 20 to 35 years previously, to identify potential exposure-related neurological abnormalities. Few significant (p less than 0.05) differences existed between exposed and unexposed subjects. However, multiple linear regression analysis demonstrated several significant correlations between declining neurological function and increasing exposure as determined by urine mercury measurements from the exposure interval. Subjects with ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 23 publications
5
90
1
1
Order By: Relevance
“…The studies have mainly utilized neurological effect measures and have indicated a slight persistent impairment of the central nervous system after the cessation of exposure. The reported neurological effects have mainly been related to motor functions, such as decreased coordination and increased tremor (22)(23)(24)(25), or decreased sensation (22,24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies have mainly utilized neurological effect measures and have indicated a slight persistent impairment of the central nervous system after the cessation of exposure. The reported neurological effects have mainly been related to motor functions, such as decreased coordination and increased tremor (22)(23)(24)(25), or decreased sensation (22,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Little research on previously exposed subjects has been published. There is, however, evidence of persisting neurological abnormalities in subjects with past exposure (22)(23)(24)(25). In addition, evidence of persisting neurobehavioral impairment in former Japanese mercury miners, especially motor coordination, has been presented (26).…”
mentioning
confidence: 99%
“…These brief periods of high exposure may actually be responsible for the neurological damage that is revealed by neurobehavioral tests. The number of peak exposure events has been shown by Albers et al (1988) to be a better predictor of neurological effects associated with exposure to mercury than mean or cumulative Hg exposure levels. The Echeverria et al…”
Section: Effects Of Past Peak Exposuresmentioning
confidence: 99%
“…Nervous system and kidney HgU of > 500 µg/L in the previous year Langolf et al [17] Nervous system -Impaired performance on visual memory tasks HgU peaks > 100 µg/L Forzi et al [18] Nervous system-Abnormal reflexes, decreased coordination HgU > 600 µg/L Albers et al [19] Postural and intention tremors HgU mean of 63 µg/L Roels et al [20] Kidneys (Excretion of high and low molecular weight proteins) Biological permissible limit of 200 µg/L Schaller et al [21] Kidneys (Glomerular type proteinuria) HgU > 50 µg/g creatinine Berode et al [22] Buchet et al [23] Impaired performance in memory tasks Group means HgU 56 µg/L. Piikivi et al [24] CNS and Kidneys HgU > 50 µg/g creatinine Roels et al [25] whose HgU had exceeded 500 µg/L in the previous year.…”
Section: Target Organ Threshold Limit For Hgu Referencementioning
confidence: 99%